1990
DOI: 10.1021/tx00015a006
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of nucleoside-carcinogen reactivity. Alkylation of adenine, cytosine, guanine, and thymine and their deoxynucleosides by alkanediazonium ions

Abstract: MNDO semiempirical molecular orbital calculations for the SN2 alkylation of nucleic acid bases and deoxynucleosides by the methane-, ethane-, and propanediazonium ions are presented. An approximate correlation is demonstrated between the calculated relative activation enthalpies for attack at alternative base sites and the related experimental quantities for DNA modification by alkylnitrosoureas. The empirically observed shift from N- to O-alkylation with increasing complexity of the alkylating agent is reprod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
52
5

Year Published

1994
1994
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 47 publications
2
52
5
Order By: Relevance
“…A strong dependence of the specificity of alkylation on the nature of the alkylating species has been repeatedly found in early works on alkylation of nucleobases by carcinogens. [29][30][31][32] Agents that are not particularly ionic in nature mainly alkylate sites with a high relative nucleophilicity through a bimolecular displacement (S N 2) mechanism, whereas electrophiles with more ionic character prefer to react at the less nucleophilic sites. Owing to the presence of a positive charge on the oxygen atom of the dioxane moiety linked to B-8 of the metallacarborane complex, the electron density at C-1 of dioxane is strongly decreased.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A strong dependence of the specificity of alkylation on the nature of the alkylating species has been repeatedly found in early works on alkylation of nucleobases by carcinogens. [29][30][31][32] Agents that are not particularly ionic in nature mainly alkylate sites with a high relative nucleophilicity through a bimolecular displacement (S N 2) mechanism, whereas electrophiles with more ionic character prefer to react at the less nucleophilic sites. Owing to the presence of a positive charge on the oxygen atom of the dioxane moiety linked to B-8 of the metallacarborane complex, the electron density at C-1 of dioxane is strongly decreased.…”
Section: Resultsmentioning
confidence: 99%
“…An additional aspect which should be taken into consideration is the increase of the hardness of the electrophilic carbon center in dioxane due to the proximity of the oxonium oxygen atom and therefore preferential reaction with the harder oxygen ionic center of the thymine or guanine base than with the softer nitrogen one. [30][31][32][33] The site for base alkylation in the final products 8 a-c derived from 3 a-c was determined by comparing the UV spectra of 8 a-c ( Table 2) with those of other alkylation products described in the literature, [29] and was subsequently confirmed by NMR spectroscopy using the HMBC technique to analyze the fully protected precursors 3 a-c. First, the signals of the methylene groups of the 3-oxapentoxy linker were assigned in the 1 H and 13 C NMR spectra using 1 H-1 H COSY and DEPT techniques for designating signals in the 13 C NMR spectrum. The DEPT procedure was applied to distinguish between CH (DEPT 90) and CH 2 (DEPT 135) groups.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Ford and Scribner [26] have used MNDO calculations in studies of nucleobases' alkylation by alkylnitrosoureas. They have shown that optimal geometry of the transition state determines the preferences for either oxygen or nitrogen attack by these agents.…”
Section: Introductionmentioning
confidence: 99%
“…2,5,9,10 However, for many alkylating agents, reaction at guanine O 6 represents less than 10% of the total alkylation in DNA and RNA. [4][5][6][7][8] The methane diazonium ion, CH 3 N 2 þ , is the reactive intermediate formed from MeNU, 3,[11][12][13][14][15] N-methyl-N 0 -nitro-N-nitrosoguanidine (MNNG), 16 methylnitrosocarbamates, 17 trimethyltriazenes, 18 and nitrosamines. 17 This intermediate undergoes sequence specific reactions with guanine N7 and guanine O 6 in DNA.…”
Section: Introductionmentioning
confidence: 99%